Modalización de los verbos en infinitivo en el castellano andino - Esquivel Villafana, Jorge (2011)
In the present work, we permit offers them the description of a phenomenon of syntactic cut registered in the Castilian of Ayacucho, consisting of the employment of the verbal forms brought together of the subjunctive for not personal pronouns of the infinitive, which we have given in presenting it as a case of modalization of the verbs in infinitive in the Andean Castilian.